2017
DOI: 10.1111/head.13207
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Headache and Sleep Disturbance: A Comparison of Diagnostic Groups

Abstract: Assessment and treatment of sleep problems in pediatric patients with chronic headache is important with several contextual and headache diagnostic factors influencing the severity of sleep disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 53 publications
2
27
1
Order By: Relevance
“…If an association between psychiatric comorbidities and excess healthcare expenditures can be established, future studies could aim to understand whether treating psychiatric comorbidities reduces potentially avoidable healthcare expenditures among youth with headache. There are known modifiable psychosocial and behavioral factors that influence the onset and maintenance of headache in youth (eg, coping skills, lifestyle factors such as sleep, parent and family distress, and adherence to daily preventive medications [30][31][32][33][34] ). However, whether treatment targeting these factors can influence healthcare expenditures in youth with headache is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…If an association between psychiatric comorbidities and excess healthcare expenditures can be established, future studies could aim to understand whether treating psychiatric comorbidities reduces potentially avoidable healthcare expenditures among youth with headache. There are known modifiable psychosocial and behavioral factors that influence the onset and maintenance of headache in youth (eg, coping skills, lifestyle factors such as sleep, parent and family distress, and adherence to daily preventive medications [30][31][32][33][34] ). However, whether treatment targeting these factors can influence healthcare expenditures in youth with headache is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest the article "Pediatric headache and sleep disturbance: a comparison of diagnostic groups" by Rabner et al 1 A large number of patients is studied with different tools that allow a useful analysis of some important comorbidities. I am surprised by the high number of patients (n = 92) having diagnosis of "new daily persistent headache (NDPH)," in the absence of patients with other forms of chronic headaches.…”
Section: Comments Observations and Rebuttals New Daily Persistent Hmentioning
confidence: 99%
“…The Nord‐Trøndelag Health Study (HUNT) has shown that every third adolescent experiences recurrent headaches (Zwart, Dyb, Holmen, Stovner, & Sand, ). Chronic headaches in adolescents can have consequences such as absence from school, inability to maintain social activities (Bruijn et al, ; Roth‐Isigkeit, Thyen, Stöven, Schwartzenberger, & Schmucker, ), and additional disorders such as anxiety, depression, problems sleeping, and reduced quality of life (Bellini et al, ; Blaauw et al, ; Rabner, Kaczynski, Simons, & LeBel, ).…”
Section: Introductionmentioning
confidence: 99%